2015
DOI: 10.2196/humanfactors.4537
|View full text |Cite
|
Sign up to set email alerts
|

Usability Testing of a Complex Clinical Decision Support Tool in the Emergency Department: Lessons Learned

Abstract: BackgroundAs the electronic health record (EHR) becomes the preferred documentation tool across medical practices, health care organizations are pushing for clinical decision support systems (CDSS) to help bring clinical decision support (CDS) tools to the forefront of patient-physician interactions. A CDSS is integrated into the EHR and allows physicians to easily utilize CDS tools. However, often CDSS are integrated into the EHR without an initial phase of usability testing, resulting in poor adoption rates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 24 publications
1
53
0
Order By: Relevance
“…It is thus crucial to devise computerized tools that are optimally integrated into clinician workflow without causing alert fatigue [3] and that usability may be as important as accuracy and effectiveness in implementing CDS [11]. We speculate that the high adoption rates of 29-42% in our study, as opposed to an average of 10-20% adoption from previous CDS research [9], were a result of the comprehensive user centered development process including workflow assessment of the emergency department, focus groups, usability testing, and collaboration with a multidisciplinary team [23,27,31].…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…It is thus crucial to devise computerized tools that are optimally integrated into clinician workflow without causing alert fatigue [3] and that usability may be as important as accuracy and effectiveness in implementing CDS [11]. We speculate that the high adoption rates of 29-42% in our study, as opposed to an average of 10-20% adoption from previous CDS research [9], were a result of the comprehensive user centered development process including workflow assessment of the emergency department, focus groups, usability testing, and collaboration with a multidisciplinary team [23,27,31].…”
Section: Discussionmentioning
confidence: 74%
“…As our past research study has shown, usability testing prior to integration of the tool can lead to high adoption rates [3]. Thus we implemented a two-phase usability testing approach with emergency physicians prior to the integration of the Wells' CPR into the EHR [31]. Furthermore, the "sensitivity and specificity trigger analysis" (SSTA) was developed to identify optimal trigger locations to avoid underutilization and overtriggering [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are related evidences that the usability of CDSS should be evaluated since it is determined as the successful implementation of CDSS [12], [13]. Authors in [12] evaluate usability of CDSS by conducting two phases of usability testing.…”
Section: B Relevant Research: Assessment Of Cdss Applicationmentioning
confidence: 99%